The Practice of Bribery in the Issuance of Driver's Licenses by Students Reviewed from the Perspective of Community Legal Culture - Hikma Nurrohmah Putri; Ninejulianggi Trinandita Iswahyuni; Gerry Lazuardi; Desinta Dwi Rapita (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2026)
The practice of bribery in the issuance of Driver's Licenses in Indonesia is a form of corrupt behavior that has taken root in the bureaucratic culture and society. Based on data from the 2024 Anti-Corruption Behavior Index, it was recorded that 30.96% of the public still consider it reasonable to give money to the authorities to facilitate the processing of Driver's Licenses and other legal documents. This fact shows that corrupt behavior has become part of the legal culture of Indonesian society. This study aims to examine 1) Procedures for Issuing Driver's Licenses based on the National Police Regulation of the Republic of Indonesia Number 5 of 2021 concerning the Issuance and Marking of Driver's Licenses, 2) Implementation of Bribery Practices in Issuance of Driver's Licenses, 3) Reasons for Giving Bribes in the Issuance of Driver's Licenses Reviewed from the Legal Culture of the Community. The research method was carried out with qualitative methods and data collection through questionnaires. The results of the study found that: 1) the procedure for issuing a Driver's License based on the Regulation of the National Police of the Republic of Indonesia Number 5 of 2021 concerning the Issuance and Marking of a Driver's License which explains the process of issuing a Driver's License through administrative stages, health tests, and exams consisting of theoretical exams and practical exams 2) The implementation of the practice of bribery in issuing a Driver's License is carried out through police officers or brokers by providing money so that the applicant does not go through the theoretical exam and practical exam stages 3) Most of the respondents do